2006
DOI: 10.29333/ejgm/82354
|View full text |Cite
|
Sign up to set email alerts
|

Open Prostatectomy: The Results Of A Series Of 320 Cases In Rural Area

Abstract: Aim: Suprapubic prostatectomy is frequently performed in areas with poor socioeconomic condition due to insuficient endoscopy equipment. The aim of this retrospective study is to analyse and bring our experience about the open prostatectomy operation Methods: A retrospective study was done on 320 consecutive patients with BPH underwent open prostatectomy operation between January 1996 and December 2002. Analyzed factors were age, complaints, comorbidities (especially cardiac and respiratory), early and late co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Our total complication rate was 90 (36.4%). Ceylan et al [24], in a review of OP in Asia reported a total complication rate of 34.6%, while researchers on the African continent have reported values between 40.1% and 42.3% [16] [22]. The modified Clavien system popularized by Dindo et al [7] was used to classify the complications from our study ( Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…Our total complication rate was 90 (36.4%). Ceylan et al [24], in a review of OP in Asia reported a total complication rate of 34.6%, while researchers on the African continent have reported values between 40.1% and 42.3% [16] [22]. The modified Clavien system popularized by Dindo et al [7] was used to classify the complications from our study ( Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…As a corollary, it can thus be inferred that while suture technique alone is ineffective in achieving hemostasis, traction at the bladder achieves hemostasis. 12 Traction at the bladder neck also has the advantage of allowing normal involution of prostatic fossa and thus aids in ensuring complete hemostasis which is the significant advantage over the technique of keeping inflated balloon in the prostatic fossa, wherein this normal involution is hampered and rebound hemorrhage is common. Goodyear and Beard have shown by the means of serial postoperative urethrogram of prostatic fossa, like the uterus, contracts to 50 percent of its size within few minutes, to 25% in 6 to 12 hours and gradually it contracts completely.…”
Section: Resultsmentioning
confidence: 99%
“…10 Open prostatectomy is superior over TURP for symptomatic relief and improvement of urination, but it is an invasive procedure and high morbidity compared to transurethral prostate resection. 11 Complete medical history, physical examination including the digital rectal examination (DRE), laboratory investigations including Total Prostate Specific Antigen (TPSA), renal function tests, and urine analysis and ultrasound are obligatory work-up for the diagnosis of BPH as coincided by the World Health Organization (WHO) sponsoredInternational consensus committee (ICC), UK British prostate group and American guideline group. 8 Suspect or presence for bladder cancer and/or prostate cancer is contraindicated of open simple prostatectomy.…”
Section: Discussionmentioning
confidence: 99%